High-Molecular-Weight Plasmid Correlates with Escherichia coli Enteroinvasiveness - Harris, Jeffrey R. (1982)
We tested by the Sereny method and examined for plasmids 14 previously Sereny-test-positive and 17 previously untested Escherichia coli strains. The presence of a 140-megadalton plasmid was significantly associated with enteroin-vasiveness as measured by the Sereny test in the 31 E. coli strains examined.